2019
DOI: 10.5123/s1679-49742019000100013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da implantação do Sistema de Informações sobre Mortalidade no estado de Pernambuco em 2012*

Abstract: Objective: to evaluate the implantation of the Mortality Information System (SIM) in Pernambuco, Brazil. Methods: this was an evaluation study; primary data (questionnaires) and secondary data (SIM) were used for the municipalities to estimate the degree of implantation (DI), comparing structure and process indicators with outcome indicators; data were consolidated by region and state. Results: SIM was partially implanted in the state (70.6%) and its regions (66.3% to 74.8%); 'management' (75.1%), 'issuing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
3
0
7
Order By: Relevance
“…more partnerships with other sources of information) 32 . However, Figueiroa et al already observed an increase in over 90% of the SIM coverage 32,33 . For this reason, the information in the studies by Figueroa et al 32,33 , partially explains the results observed in Figures 1 and 2 of this study.…”
Section: Discussionmentioning
confidence: 92%
“…more partnerships with other sources of information) 32 . However, Figueiroa et al already observed an increase in over 90% of the SIM coverage 32,33 . For this reason, the information in the studies by Figueroa et al 32,33 , partially explains the results observed in Figures 1 and 2 of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Em outros estudos que avaliaram a implantação do SIM, a ausência de capacitação dos recursos humanos, de supervisão e controle, e a alta rotatividade Cad. Saúde Pública 2022; 38(2):e00356120 de técnicos para o gerenciamento da informação, foram encontrados em nível municipal como fatores que comprometeram a implantação do SIM na sua inteireza 25,26,27 .…”
Section: Discussionunclassified
“…The coverage of vital information in Pernambuco is considered high, 16 and the level of Sinasc and SIM implementation is adequate. 17 The method used may not official information systems, its implementation as a neonatal care surveillance tool that can monitor and compare the performance of health care facilities over time becomes easier. Other existing definitions make data collection more complex, hindering its routine use in health services.…”
Section: Discussionmentioning
confidence: 99%